Severe Influenza Patients Who Received Ventilator Management During the 2024 to 2025 Major Influenza-Endemic Season in a Tertiary Hospital in Japan - Seki M; Shimada D (International Medical Case Reports Journal, 2025)
Masafumi Seki,1 Daishi Shimada2 1Division of Infectious Diseases and Infection Control, Saitama Medical University International Medical Center, Hidaka City, Japan; 2Division of Respirology, Tohoku Medical and Pharmaceutical University, Sendai City, JapanCorrespondence: Masafumi Seki, Division of Infectious Diseases and Infection Control, Saitama Medical University International Medical Center, Yamane, 1397-1, Hidaka City, Saitama, 350-1298, Japan, Tel +81-42-984-4392, Fax +81-42-984-0280, Email sekimm@saitama-med.ac.jpAbstract: Three cases of severe influenza that required ventilator management in the 2024– 2025 season, which was a major influenza season in Japan, are presented. Case 1: A 54-year-old man with obesity developed lobar pneumonia as a result of severe community-acquired pneumonia (CAP) secondary to methicillin-susceptible Staphylococcus aureus (MSSA), as confirmed on sputum culture. The nasal swab was positive for influenza A antigen. Intravenous peramivir and piperacillin/tazobactam were administered for 2 days followed by lascufloxacin and linezolid for 2 weeks. Veno-venous extracorporeal membrane oxygenation (VV-ECMO) was also performed. Case 2: A 63-year-old man with multiple myeloma and chronic kidney disease developed severe pneumonia as a result of CAP. Although influenza A antigen was detected, no bacteria were isolated from his specimens. He showed severe hypoxia and massive ground-glass opacities (GGOs) in both lung fields, but he recovered after administration of peramivir and levofloxacin with prednisolone for 2 days and 2 weeks, respectively, with non-invasive positive pressure support. Case 3: A 43-year-old man without any related medical history developed severe heart failure with mild bronchopneumonia and was admitted to our hospital. Acute heart failure caused by myocarditis and CAP due to influenza A were suspected and treated effectively with peramivir and a percutaneous ventricular assist device (IMPELLA), which involved an auxiliary circulating pump with veno-arterial ECMO (VA-ECMO) for 1 day and 2 weeks, respectively. In three middle-aged patients, influenza virus may have accelerated pneumonia/heart failure. All three patients had not received influenza vaccines and were not elderly. Although the emphasis on most vaccines has decreased after the COVID-19 pandemic appears to have subsided, we should stress the importance of influenza vaccines and improvement of critical care protocols, because severe influenza can be a concern for young and middle-aged adults during the influenza season after the post COVID-19 pandemic period.Keywords: influenza, peramivir, extracorporeal membrane oxygenation, ECMO, myocarditis, pneumonia, vaccine